2015
DOI: 10.5370/jeet.2015.10.4.1720
|View full text |Cite
|
Sign up to set email alerts
|

Capacitance Swing and Capacitance Ratio of GaN-Based Metal-Semiconductor-Metal Two-Dimensional Electron Gas Varactor with Different Dielectric Films

Abstract: -The performance of the AlGaN/GaN MSM-2DEG varactor with different dielectric films deposited by the E-beam deposition is investigated in detail. The capacitance swing and the capacitance ratio of the varactor without dielectric film as well as with, SiO 2 , Gd 2 O 3 , and Si 3 N 4 films, respectively, are determined by electrodes of varying areas. The maximum capacitance, the minimum capacitance and the capacitance ratios are proportional to the increasing of the electrode areas. The capacitance ratio determi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2017
2017
2020
2020

Publication Types

Select...
2
2

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 17 publications
0
1
0
Order By: Relevance
“…In this context, this thesis research is focused to demonstrate the use of Chapter III In 2015, by the same group researchers of [55], a MSM varactor study has been reported in [56]. Based on Schottky barrier, another work was reported in [58].…”
Section: Use Of Gan In Reconfigurable Rf/microwavementioning
confidence: 99%
“…In this context, this thesis research is focused to demonstrate the use of Chapter III In 2015, by the same group researchers of [55], a MSM varactor study has been reported in [56]. Based on Schottky barrier, another work was reported in [58].…”
Section: Use Of Gan In Reconfigurable Rf/microwavementioning
confidence: 99%